Motor control characteristics for circular tracking movements of human wrist. (17th January 2017) - Kim, Jihun; Lee, Jongho; Kakei, Shinji; Kim, Jaehyo
Abstract: This paper investigates motor characteristics during circular tracking movements of human wrist. Ten subjects performed a visually guided target tracking task using two degrees-of-freedom wrist movements as a tracer. Based on trajectories of the tracer and the target, three control parameters in polar coordinates were considered: R error as an evaluation of the circular movement performance, theta error of the position-control precision, and omega error of the velocity-control precision. We then examined the influence of three different speeds (0.05, 0.1, and 0.2 Hz) and visibility of the target on the three parameters to observe changes in control strategy. The theta error particularly demonstrated that subjects were more dependent on position control for the lower tracking speed of 0.05 Hz with a visible target, where the highest percentage increase of 210.6% in theta errors from the target visible to the target invisible regions was reported. However, as the target speed increases, the subjects concentrated more on the velocity of the target as a main control parameter, and a minimum percentage decrease of 9.52% in the omega error appeared from target visible to target invisible regions for 0.2 Hz. The results suggest that velocity control is more dominant during target invisible or fast tracking task. Abstract :